2018
DOI: 10.1152/ajpheart.00680.2017
|View full text |Cite
|
Sign up to set email alerts
|

Coronary microvascular dysfunction in patients with heart failure with preserved ejection fraction

Abstract: There are multiple proposed mechanisms for the pathophysiology of heart failure (HF) with preserved ejection fraction (HFpEF). We hypothesized that coronary microvascular dysfunction is common in these patients. In a prospective, observational study, patients undergoing cardiac catheterization with HFpEF [left ventricular (LV) ejection fraction ≥ 50% and with clinical HF] were compared with similar patients without HFpEF. Patients with ≥50% stenosis were excluded, and coronary flow reserve (CFR) and the index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 47 publications
3
73
0
2
Order By: Relevance
“…Recent studies, editorial commentaries and reviews have begun to embrace the potential importance of CMD in the pathophysiology of HFpEF . In an autopsy study, patients with HFpEF displayed a higher prevalence of microscopic hypertrophy, coronary microvascular rarefaction, and fibrosis than age‐matched controls .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies, editorial commentaries and reviews have begun to embrace the potential importance of CMD in the pathophysiology of HFpEF . In an autopsy study, patients with HFpEF displayed a higher prevalence of microscopic hypertrophy, coronary microvascular rarefaction, and fibrosis than age‐matched controls .…”
Section: Discussionmentioning
confidence: 99%
“…endothelin), while endothelium‐independent dysfunction depends on vascular myocyte tone and other factors . Although a number of studies have revealed that endothelium‐independent CMD is present on average in patients with HFpEF, both non‐invasively and invasively, no study has yet specifically evaluated endothelium‐dependent coronary microvascular function. The current study confirms and extends upon these earlier studies by demonstrating impaired CFR as measured directly in a much larger cohort of patients, while demonstrating for the first time in HFpEF that coronary endothelium‐dependent vasodilatation is also impaired in a substantial proportion of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, change of %FMD was not associated with change of E/e ′ in the present study. It is possible that for the evaluation of endothelial function of small vessels, for example, the peripheral arterial tonometry ratio might be more suitable, as coronary microcirculation impairment participates in left ventricular diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…A key point of the study is that CMD, similarly to HFpEF, can be manifold and the existence of different CMD forms in HFpEF should be identified in order to unravel its role and weight in the pathophysiology of HFpEF. Accordingly, Dryer et al . recently demonstrated the presence of four distinct coronary physiology groups in HFpEF patients combining invasive measurements of CFR and index of microvascular resistance.…”
mentioning
confidence: 99%